ANALISA JARINGAN FIBER OPTIK DI TELKOM AKSES MENGGUNAKAN METODE FISHBONE - Maksi Surya Pratama; Jeffri Alfa Razaq (STEKOM PRESS, 2023)
The internet is a computer network system that is connected to each other. To achieve an internet, you need a fiber optic network that can transfer certain information data up to speeds of up to 100Mbps. However, customer service often receives customer complaints regarding unstable Indihome network services in the Banyumanik STO area. So it is necessary to do research on Fiber Optic Network Analysis from Server to Optical Network Terminal (ONT) at PT Telkom Access Banyumanik STO Using the Fishbone Method. To analyze the causes that affect the quality of fiber optic network for good or bad. Network quality analysis was carried out using the Fishbone Diagram method as a basis for obtaining the results of measuring the quality of fiber optic networks at ODC BMK FAE/ODP BMK FAE 016 Jalan Banjarsari Barat – Jalan Tembalang Selatan. The results of network quality analysis through brainstorming sessions with 11 employees of PT Telkom Access obtained an average answer of 92%. Then measure the quality of the network in the field, namely from the Optical Line Terminal (OLT) to the Customer. The results obtained are directly proportional to the standard network quality analysis with an attenuation value of -19.10 dBm. So it can be concluded that the case study area has good network quality because the results of the average value of the questionnaire answers and the measurement results of the case study area have a value above the standard.